Financial sector development and economic growth in Indian states. (1st January 2013) - Bhanumurthy, N.R.; Singh, Prakash
The present study tries to understand the trends and determinants of economic growth in the Indian states in the post-reform period. For this, it considers the role of financial sector development since this sector has seen substantial reform measures. With the help of panel time series models, the study concludes that there is a long run relationship between financial variables and the growth. The results also show, although it is necessary to have development in terms of increase in number of bank branches, it is the extent of bank business which is more important in the growth process at the state level. In other words, financial sector reform that improves financial intermediation could have substantial growth impact in state output and expansion of bank branches could just be a necessary but not a sufficient condition when we look from the macroeconomic growth perspective. Further, as empirical results show that there is a bidirectional causation between growth and finance, policy measures are needed to enhance access that ensures positive and stable relationship between these two.